A COMPARISON ANALYSIS OF PURCHASE DECISION OF WOMEN COSMETIC PRODUCTS IN MANADO (CASE STUDY KOREAN COSMETIC AND INDONESIAN COSMETIC BRAND) - BURHANUDDIN, HELMY CABRINA (Jurnal Berkala Ilmiah Efisiensi, 2016)
The lifestyle nowadays has been changing rapidly along with the development of globalization. Every year, the perspective of beauty is always growing, not only as a desire or wants but it has become daily needs for all women and it has been one of the most important beauty hallmarks. It could even be said that women and cosmetic are inseparable. Women are very concerned about skin and beauty and want to always look good and fresh. The objective of this research is to analyze the difference in purchase decision between Korean Cosmetic Brand and Indonesian Cosmetic Brand on Price, Social Influences, Celebrity Endorsement, and Product Packaging. The method analysis on this research is Independent T-Test to compare Korean Cosmetic and Indonesian Cosmetic Brand in Manado. The sampling method is convenience sampling as many as 200 respondents. The result concluded that there is no significant difference in purchase decision on price and social influence between Korean cosmetic brand and Indonesian cosmetic brand, but there is a significant difference in purchase decision on celebrity endorsement and product packaging between Korean cosmetic brand and Indonesian cosmetic brand. The research recommend the marketers of both brands, which are Korean cosmetic brand and Indonesian cosmetic brand, should consider more on the factors that influence the purchase decision.